Adsorption of Methylene Blue on Nano Composite MWCNTs/ZrO2: Equilibrium, Dynamic and Surface Data - Chen1, Pinghua; Zhou1, Xuezhen; Li1, Dongping; Li1, Jing; Liu1, Yanzhu; Li1, Yongxiu (Asian Journal of Chemistry, 2014)
A directly ball milling method for quick synthesis of multiwall carbon nanotubes (MWCNTs)/ZrO2 composite was developed in this study. The adsorption ability of the composite was determined taking methylene blue as model contaminant. Results show the adsorption ability of material could be improved by almost 1.5 times by this simple method. The composite was characterized by TEM, EDS, XRD, Zeta-potential and surface area. The equilibrium adsorption isotherms, kinetic and thermodynamic properties, adsorption mechanism of the related adsorption process were investigated. Results show the adsorption reaction is a spontaneous, endothermic and physisorption process. Based on the low cost and simple peparing method, the nano composite is considered to be a promising adsorbent to treat water pollution in large scale.